Analysis of Budget Performance Achievements of Public Service Agency (BLU) University Of Pattimura 2019-2024 - Hitijahubessy, Martha Maria; Asnawi, Raden Ayu Aisah; Tetelepta, Silva (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study aims to evaluate the level of fiscal independence, effectiveness, and efficiency of PNBP fund management at Pattimura University during the 2019–2024 period. The research method uses a quantitative descriptive approach with financial ratio analysis techniques according to the Value for Money approach. Data were obtained through documentation of budget reports and realization, observation, and interviews. The results of the study indicate that the level of fiscal independence of Pattimura University is in the good category with an average of 41.16%. The effectiveness of achieving PNBP targets is classified as very effective with an average of 113.14%. Meanwhile, the efficiency of PNBP fund collection shows a positive trend with a ratio of 0.02. These findings indicate that budget management at Pattimura University is increasingly accountable and performance-oriented. This study provides practical implications for strengthening higher education financial governance in the context of autonomy and BLU-based management